In vitro regeneration approaches for restoration of Ceropegia mohanramii—an endemic and critically endangered asclepiad - Avinash A. Adsul; Jaykumar J. Chavan; Nikhil B. Gaikwad; Rajaram V. Gurav; Ghansham B. Dixit; Shrirang R. Yadav (Journal of Genetic Engineering and Biotechnology, 2019)
Abstract The study aimed to develop an efficient, rapid, and large-scale in vitro regeneration system for propagation, conservation, and restoration of an endemic and critically endangered herb, Ceropegia mohanramii. The cultures were established using nodal explants on Murashige and Skoog’s (MS) medium supplemented with 6-benzylaminopurine (BAP: 1.0 mg/l). Nodal buds cultured on MS medium supplemented with BAP (2.0 mg/l) along with indole-3-butyric acid (IBA, 0.5 mg/l) resulted with production of maximum number of shoots (17.1 ± 1.2) in hundred percent of the cultures. MS medium supplemented with BAP (2.0 mg/l) along with diverse concentrations of indole-3acetic acid (IAA) promoted the in vitro flowering. In vitro regenerated shoots were transferred to one-half MS medium fortified with singular supplementation of auxins, where IBA (1.5 mg/l) served optimal for production of maximum number of roots (5.7 ± 0.6). In vitro derived plantlets were hardened under controlled conditions in a glasshouse and subsequently transferred to soil. Over 1200 saplings were transplanted to eight different localities of the Western Ghats where over 76% survival is recorded after 1 year of transplantation.